Early Detection of Major Fetal Structural Anomalies in the First Trimester: A Retrospective Single-Center Study in an Unselected Population - Maciej Korniluk; Andrzej Korniluk; Grzegorz Szewczyk (Journal of Clinical Medicine, 2026)
Background: The first-trimester ultrasound (11 + 0 to 13 + 6 weeks) is primarily used for aneuploidy screening, yet its potential for early identification of major fetal structural anomalies in an unselected population continues to be explored. This study evaluated the clinical yield and feasibility of a systematic first-trimester fetal anatomy assessment in a regional setting. Methods: This retrospective single-center study included 500 consecutive singleton pregnancies undergoing routine first-trimester ultrasound between 11 + 0 and 13 + 6 weeks of gestation. All examinations were performed by a single certified sonographer using an extended anatomical protocol according to ISUOG and FMF guidelines. The study center serves a regional population of approximately 400,000 inhabitants in eastern Mazovia, Poland. Cases with suspected anomalies underwent a detailed diagnostic work-up, including a targeted anomaly scan, early fetal echocardiography, and invasive genetic testing when clinically indicated. Results: Major fetal structural anomalies were suspected in 17 out of 500 fetuses (3.4%) during the first-trimester scan. Of the 17 suspected cases, 14 were confirmed on subsequent evaluation (14/17, 82.4%; 95% CI 56.6–96.2%), two were false-positives (11.8%), and one patient was lost to follow-up. Four fetuses (23.5%) presented with multiple anomalies involving different organ systems, with congenital heart defects being the most prevalent. A notable observational cluster of three cases of acrania/exencephaly was identified. Remarkably, only three of the confirmed affected cases (21.4%) presented with a nuchal translucency measurement above the 95th percentile. Conclusions: Integration of a systematic first-trimester fetal anatomy assessment allowed the identification of suspected major structural anomalies in 3.4% of fetuses in an unselected regional population. With a confirmation rate of 82.4% among screen-positive cases, these findings demonstrate the clinical feasibility of detailed first-trimester anatomical assessment in a regional setting.